Revisited the relationship between vitamin D level and receptors of BsmI- gene polymorphism with the pathogenetic mechanisms of placental dysfunction development - Manasova, G. S.; Zelinsky, A. A.; Didenkul, N. V.; Artemenko, V. V.; Makshayeva, E. T. (Journal of Education, Health and Sport, 2018)
The role of the calcitriol / vitamin D receptor (VD) endocrine system and the pleiotropic effects of this system in the pathogenetic mechanisms of various diseases development, in particular complications of pregnancy, has attracted researches’ increasing attention in recent years. The aim of the work: to compare the VD-status and frequency of occurrence of polymorphism of the VDR gene (BsmI (A> G, rs1544410) in patients with a physiological course of the gestation process and in patients with placental dysfunction (PD). Materials and methods. 56 pregnant women with PD (the main group) and 40 patients with a physiological pregnancy (control group) were examined. VD status was determined by ELISA at level 25 (OH) D in serum, the frequency of BsmI polymorphism of the VDR gene (rs1544410) by polymerase chain reaction (PCR). Results. The average index of VD (31.40 ± 8.6) ng / ml in patients with PD is significantly lower than in patients with physiological pregnancy (43.54 ± 11.20) ng / ml, (p ≤ 0.05 ). In patients with PD, homozygous carrier for the A-allele was found in 12% of cases, in healthy pregnant women - in 16.7%, (р ≥ 0.05), for the G-allele - in 20% and 47.20%, (р ≤ 0.01) cases, respectively to groups. Heterozygous combination of A / G alleles was noted in 68% of patients with PD and in 36.10% of the control group patients. In pregnant women with BsmI polymorphism of calcitriol gene (genotype A / G) PD was 3.7 times more frequent (68% vs 36.10% : RR = 2.1, CI 1.0-6.6, OR = 3.7, CI 1.1-13.1). Conclusions. Vitamin D insufficiency or deficiency can be one of the reasons of PD formation. In carriers of BsmIgene’s polymorphism encoding VD receptor with genotype A / G, the course of pregnancy is complicated by placental dysfunction 3.7 times more often than in women without this polymorphism.